Efektivitas pemasaran berbasis digital pada industri perbankan syariah - Qomariyah, Rif'atul (Maliki Interdisciplinary Journal, 2025)
The rapid advancement of digital technology has significantly transformed marketing strategies within Islamic banking. Digital marketing management focuses on the processes of planning, implementation, monitoring, and evaluation of marketing activities through various online platforms, including social media, websites, mobile applications, search engine optimization (SEO), email marketing, and digital advertising. Through the integration of financial technology (fintech), Islamic banks are able to enhance service efficiency, expand market reach, and build stronger engagement with customers. Digital platforms also enable Islamic banks to highlight key values such as fairness, transparency, and Sharia compliance, providing a competitive advantage within the increasingly dynamic financial industry. However, the digital era presents several challenges, including the need for highly skilled human resources, cybersecurity threats, consumer protection issues, and gaps in financial literacy among the public. On the other hand, substantial opportunities arise from the large number of internet users, growing interest of younger generations in digital services, and the ability of Islamic banks to provide products that align with technological developments and modern financial needs. With continuous innovation and effective digital marketing strategies, Islamic banks can strengthen competitiveness and enhance their position within the national financial sector